2018
DOI: 10.3390/molecules24010075
|View full text |Cite
|
Sign up to set email alerts
|

Micro-/Nano-Scales Direct Cell Behavior on Biomaterial Surfaces

Abstract: Cells are the smallest living units of a human body’s structure and function, and their behaviors should not be ignored in human physiological and pathological metabolic activities. Each cell has a different scale, and presents distinct responses to specific scales: Vascular endothelial cells may obtain a normal function when regulated by the 25 µm strips, but de-function if the scale is removed; stem cells can rapidly proliferate on the 30 nm scales nanotubes surface, but stop proliferating when the scale is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 115 publications
0
40
0
Order By: Relevance
“…The micro-scale patterns can profoundly influence the overall cell morphology; however, the nano-scale topographies are more critical in controlling the molecular and subcellular physicochemical sensing pathways. 182,185 Padmanabhan et al 186 investigated the role of surface topography size and stiffness of metallic glass nanorod arrays on cell-cell fusion. They revealed that the topographic features in nano-scale size can dominate biochemical signals in decreasing fusion through controlling cytoskeletal remodeling-associated signaling pathways.…”
Section: Impact Of Biomaterials Surface Physical Properties On Biologimentioning
confidence: 99%
“…The micro-scale patterns can profoundly influence the overall cell morphology; however, the nano-scale topographies are more critical in controlling the molecular and subcellular physicochemical sensing pathways. 182,185 Padmanabhan et al 186 investigated the role of surface topography size and stiffness of metallic glass nanorod arrays on cell-cell fusion. They revealed that the topographic features in nano-scale size can dominate biochemical signals in decreasing fusion through controlling cytoskeletal remodeling-associated signaling pathways.…”
Section: Impact Of Biomaterials Surface Physical Properties On Biologimentioning
confidence: 99%
“…[ 54,55 ] However, most of the studies have been conducted on the topographies only in a single micro‐ or nanoscale. Though a few studies have reported the regulation of stem cell behaviors on the micro/nano combined multiscale structures, [ 56–59 ] the previous micro/nano multiscale groove patterns involved sharp edges due to the characteristic of the conventional micro/nano‐fabrication techniques, such as UV lithography. These multiscale groove patterns with the sharp edges cannot be found in the natural ECM which has rather a smooth groove shape like the present SIMNs.…”
Section: Resultsmentioning
confidence: 99%
“…Wherein, SA and SP show larger pore diameters and thicker pore walls compared with SPS. The surface morphology of the SA, SP and SPS hydrogel sphere is compact in the micro sizes and there are obvious wrinkles (Figure 4b), which is completely different from the morphology of the existing porous, coherent and open hydrogels [26]. The latter, as scaffolds for tissue engineering, often promotes cell migration, proliferation and differentiation [27], while the former, as a targeted anti-tumor biomaterial, should inhibit cell growth to avoid prolonged retention of SPS spheres and their absorbed copper ion in vivo.…”
Section: Resultsmentioning
confidence: 99%